Activities for teaching psychology and law a guide for instructors - Zelechoski, Amanda D.; Wolbransky, Melinda; Riggs Romaine, Christina L. (Washington, DC American Psychological Association, 2018)
"This book presents a wide variety of experiential learning activities to help instructors enliven their courses and teach critical concepts in psychology and law. The activities incorporate individual and group work, videos, reading materials, classroom discussions, homework assignments, and lots of role play. A companion website provides free modifiable handouts and videos to support the activities. With clear instructions and guidance, this book provides everything needed to implement the activities"--Supplied by publisher.
Fact or fiction: psychology and law in the media -- Legality versus morality debate -- A brief trial -- Who do you want?: the voir dire process -- Psychological profile of a murder suspect -- Voices for victims -- To protect and serve: training law enforcement -- Do you see what I see?: eyewitness identification -- To waive or not to waive?: Miranda rights and due process -- Evaluating juvenile competency to stand trial -- A journey through civil commitment -- Do you swear to tell the truth?: expert testimony -- Can we predict?: appraising and reducing risk -- Freeze!: what's a juvenile justice facility to do? -- Problem solved?: creating a problem-solving court -- May it please the court: amicus curiae brief -- What would SCOTUS do? -- Appendix A: Written assignment grading rubric -- Appendix B: Participation grading rubric -- Appendix C: Presentation grading rubric -- Appendix D: Group and self-evaluation form -- Appendix E: Sample activity feedback survey.
Includes bibliographical references and index.
Keywords: Forensic psychology -- Study and teaching -- United States; Criminal justice, Administration of -- Study and teaching -- United States